Changes in astrocyte functional markers and β-amyloid metabolism-related proteins in the early stages of hypercholesterolemia. (1st March 2016) - Chen, Y.L.; Wang, L.M.; Chen, Y.; Gao, J.Y.; Marshall, C.; Cai, Z.Y.; Hu, G.; Xiao, M.
Highlights: Mild activation of astrocytes without neurodegeneration occurred in mice fed 3% cholesterol diet for 8 weeks. Apolipoprotein E and aquaporin 4 expression increased in the hippocampus of model mice. Levels of IL-1β, but not IL-6 and TNF-α, increased in the hippocampus of model mice. Increases in presenilin 1 and insulin-degrading enzyme in the hippocampus of the model mice. Abstract: Cholesterol is an essential substance for maintaining normal structure and function of the brain. But unfortunately, a long-term high-cholesterol diet can lead to a variety of pathological changes of the brain such as β-amyloid (Aβ) accumulation, Tau hyperphosphorylation, reactive gliosis, neuroinflammation, neuronal death and synaptic degeneration. These pathological changes have complex internal relations with one other, causing memory impairment and participating in the pathogenesis of Alzheimer's disease (AD). However, early hypercholesterolemia-induced events that lead to brain deterioration are not clear. To address this, 6-month-old female mice were fed a 3% cholesterol diet for 8 weeks, followed by behavioral, biochemical and neuropathological analyses. The high-cholesterol-fed mice did not show neuronal and synaptic impairment or cognitive deficits compared with mice given a normal diet, but astrocytes were mildly activated with increased expression of functional markers including apolipoprotein E and aquaporin 4 in the hippocampus. Hippocampal interleukin-1β expression slightly increased, but interleukin-6 (IL-6) and tumor necrosis factor-α did not change significantly compared with those in the control group. Levels of Aβ, and its precursor protein, were unaffected, but levels of presenilin 1 and insulin-degrading enzyme (IDE), that initiate Aβ generation and degradation, respectively, increased in the hippocampus of the model mice. In addition, Tau phosphorylation levels were not different between the control and model groups. These results suggest that changes in astrocyte functional markers and Aβ metabolism proteins, which contribute to maintaining brain cholesterol and Aβ homeostasis, are early events in the process of hypercholesterolemia-related neuropathological changes.